Impact of Galvanic Vestibular Stimulation on Anxiety Level in Young Adults - Pasquier, Florane; Denise, Pierre; Gauthier, Antoine; Bessot, Nicolas; Quarck, Gaëlle (Frontiers in Systems Neuroscience, 2019)
Galvanic Vestibular Stimulation (GVS) is a non-invasive method used to stimulate the vestibular system. The vestibular system includes the sensors, neural pathways, vestibular nuclei and the cortical areas receiving integrated vestibular inputs. In addition to its role in postural control or gaze stabilization, the vestibular system is involved in some cognitive functions and in emotion processing. Several studies have revealed a modulating effect of vestibular stimulation on mood state, emotional control, and anxiety level. Nevertheless, GVS is known to induce motion sickness symptoms such as nausea. The aim of the present study was to evaluate the tolerability and efficacy of a GVS protocol to be used potentially as a treatment for anxiety, and also to test the impact of stimulation parameters (duration) on anxiety. Twenty-two students underwent three stimulation conditions: 1) a sham session (no stimulation), 2) a single-duration session (38 min of GVS), and 3) a double-duration session (76 min of GVS). Before and after each stimulation, participants completed a Graybiel Scale form for motion sickness symptoms evaluation, and a visual analog scale form for anxiety. We observed a significant diminution of anxiety level after a 38-min session of GVS, while a low level of motion sickness was only found following a 76-min session of GVS. Our preliminary study confirms the feasibility of using GVS to modulate anxiety and corroborates the involvement of the vestibular system in the emotional process.